kompensasi pendidikan - rohmat rohmat (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
compensation is a kind of reward to educational worker for his/her knowledge, professionalism, time, and thought that have been dedicated to realize school commitment to produce qualified output. Compensation and teacher performance have straight relationship. The higher compensation levels the more effective teacher performance to enhancing education quality. Decentralization in education must be focused on developing local potential in every education organization. It has to develop a balanced effort to give great attention to teacher profession and remove any dichotomy in education. Teachers with state or private status have equal obligation to enhance education quality. Compensation becomes an important element to realize this objective.